Effect of lubricated polishing and repolishing on gloss, roughness and material loss of nanoparticle resin composite - de Faria, Vanessa [UNESP]; da Silva, Jefferson Pires; Caneppele, Taciana Marco Ferraz [UNESP]; Bresciani, Eduardo [UNESP] (Universidade Estadual de Campinas, 2024)
Aim: The study examined how different dry and lubricated polishing protocols impact the gloss, roughness, and material loss of nanoparticle resin composites, before and after simulated toothbrushing. Methods: One hundred cylindrical resin composite specimens were prepared and divided into an unpolished group and three test groups: Dimanto (DIM), Sof-Lex Pop-On (SOF), and Astrobrush (ASTRO). These groups underwent polishing dry, with water, or with or petroleum jelly. Surface parameters including gloss (Novo-Curve – Rhopoint TM, England), roughness, and material loss (MaxSurf XT 20, MahrGoettingen, Germany) were evaluated at four stages: baseline, polishing, simulated toothbrushing, and repolishing. Data were submitted to repeated measures ANOVA (P<0.05). Results: Lubrication did not affect the studied parameters after polishing with DIM. SOF showed improved performance without lubricants, whereas ASTRO achieved higher gloss and lower roughness when lubricated. In terms of surface material loss, DIM exhibited less material loss when used with petroleum jelly, SOF had reduced material loss when used with water, and ASTRO showed the most material loss when lubricated with petroleum jelly. Conclusion: The gloss, roughness, and surface material loss of the nanoparticle resin composite are influenced by the type of polisher used and the choice of lubricant. However, none of the differences observed surpassed the established thresholds for roughness or gloss perception, suggesting that these protocols are potentially viable for clinical application. Despite detectable differences among the polishing systems and lubricant combinations, all tested options are clinically acceptable. None of them exceeded the thresholds for biofilm accumulation or perceptible differences in surface gloss.
Keywords: Aging; Composite resins; Dental polishing; Dental restoration wear; Optical phenomena